MakerGames: A Board Game to Help Facilitators Maximize the Educational Potential of Project-based Learning. - Mueller, Matthew L. (Tufts University. Tisch Library., 2017)
The MakerGames is a board game designed to harness the power of make believe play in open-ended engineering design challenges. The four sides of the board each correspond a theme found in the traditional engineering design process; "Frame the Problem", "Make", "Evaluate", and "Share". Each tile on the board has a unique prompt that encourages storytelling to help frame the problem, brings attention to the material constraints in the building process, guides evaluation of prototypes, or facilitates sharing with marketing-type activities. Using building materials as the reward for taking turns, the players roll a die to move their piece around the board every time the game clock lands on their team. Groups briefly discuss a prompt with the facilitator before they are allowed to take a limited amount of materials, then continue building their prototype while other teams take turns at the board. To finish the game, students are guided through a series of prompts in a similar timed manner to prepare them for presentations about their creation. In this first iteration of a design based research study, the game was pilot tested in a two hour workshop at the Tufts University Center for Engineering Education and Outreach. We recorded students' conversations around the game board and collected photographs of students' fabrications during and after the game. We also collected sketches, designs, and notes made by the students. We used our data to evaluate the game's efficacy against identified criteria. The challenge used for our case study asked students to "design and build an amusement park ride for a LEGO minifigure out of LEGO and found materials". We evaluated the efficacy of the game from the points of view of both teachers and students - two populations we recognized as our design clients - focusing on how the game facilitated teaching/learning through moments experienced as "play" rather than as "work". Our initial evaluation suggests that the game effectively facilitates discussions about specific engineering design concepts in a way that allows teachers to regularly interrogate individual student's ideas in a playful way. Researchers discuss how this make believe play experience enhances learning opportunities for all participants while engaging them in higher order skills such as problem solving, working in teams, and giving presentations. © 2017 American Society for Engineering Education.